Vitamin D and Metabolic Diseases: Growing Roles of Vitamin D - Jung Eun Park; P.B. Tirupathi Pichiah; Youn-Soo Cha (Journal of Obesity & Metabolic Syndrome, 2018)
Vitamin D, a free sunshine vitamin available for mankind from nature, is capable to avert many health-related critical circumstances. Vitamin D is no more regarded as a nutrient involved in bone metabolism alone. The presence of vitamin D receptor in a number of tissues implies that vitamin D has various physiological roles apart from calcium and phosphorus metabolism. Low serum vitamin D has been found to be associated with various types of metabolic illness such as obesity, diabetes mellitus, insulin resistance, cardiovascular diseases including hypertension. Various studies reported that vitamin D insufficiency or deficiency in linked with metabolic syndrome risk. This review focuses on various metabolic diseases and its relationship with serum vitamin D status.